Intrinsic and Extrinsic Modulators of the Epithelial to Mesenchymal Transition: Driving the Fate of Tumor Microenvironment - D'Angelo, Edoardo; Lindoso, Rafael Soares; Sensi, Francesca; Pucciarelli, Salvatore; Bussolati, Benedetta; Agostini, Marco; Collino, Federica (Frontiers in Oncology, 2020)
The epithelial to mesenchymal transition (EMT) is an evolutionarily conserved process. In cancer, EMT can activate biochemical changes in tumor cells that enable the destruction of the cellular polarity, leading to the acquisition of invasive capabilities. EMT regulation can be triggered by intrinsic and extrinsic signalling, allowing the tumor to adapt to the microenvironment demand in the different stages of tumor progression. In concomitance, tumor cells undergoing EMT actively interact with the surrounding tumor microenvironment constituted by cell components and extracellular matrix as well as cell secretome elements. As a result, the tumor microenvironment is in turn modulated by the EMT process toward an aggressive behavior. The current review presents the intrinsic and extrinsic modulators of EMT and their relationship with the tumor microenvironment, focusing on the non–cells derived components, such as secreted metabolites, ECM as well as extracellular vesicles (EVs). Moreover, we explore how these modulators can be suitable targets for anti–cancer therapy and personalized medicine.